An Evolutionary Framework for Carpel Developmental Control Genes. (20th October 2016) - Pfannebecker, Kai C.; Lange, Matthias; Rupp, Oliver; Becker, Annette
Abstract : Carpels are the female reproductive organs of flowering plants (angiosperms), enclose the ovules, and develop into fruits. The presence of carpels unites angiosperms, and they are suggested to be the most important autapomorphy of the angiosperms, e.g., they prevent inbreeding and allow efficient seed dispersal. Many transcriptional regulators and coregulators essential for carpel development are encoded by diverse gene families and well characterized in Arabidopsis thaliana . Among these regulators are AGAMOUS (AG), ETTIN (ETT), LEUNIG (LUG), SEUSS (SEU), SHORT INTERNODE/STYLISH (SHI/STY), and SEPALLATA1, 2, 3, 4 (SEP1, 2, 3, 4). However, the timing of the origin and their subsequent molecular evolution of these carpel developmental regulators are largely unknown. Here, we have sampled homologs of these carpel developmental regulators from the sequenced genomes of a wide taxonomic sampling of the land plants, such as Physcomitrella patens, Selaginella moellendorfii, Picea abies, and several angiosperms. Careful phylogenetic analyses were carried out that provide a phylogenetic background for the different gene families and provide minimal estimates for the ages of these developmental regulators. Our analyses and published work show that LUG -, SEU -, and SHI/STY -like genes were already present in the Most Recent Common Ancestor (MRCA) of all land plants, AG - and SEP -like genes were present in the MRCA of seed plants and their origin may coincide with the ξ Whole Genome Duplication. Our work shows that the carpel development regulatory network was, in part, recruited from preexisting network components that were present in the MRCA of angiosperms and modified to regulate gynoecium development.